If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 2 = -8y + -11 Reorder the terms: 2 + 5y = -8y + -11 Reorder the terms: 2 + 5y = -11 + -8y Solving 2 + 5y = -11 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 2 + 5y + 8y = -11 + -8y + 8y Combine like terms: 5y + 8y = 13y 2 + 13y = -11 + -8y + 8y Combine like terms: -8y + 8y = 0 2 + 13y = -11 + 0 2 + 13y = -11 Add '-2' to each side of the equation. 2 + -2 + 13y = -11 + -2 Combine like terms: 2 + -2 = 0 0 + 13y = -11 + -2 13y = -11 + -2 Combine like terms: -11 + -2 = -13 13y = -13 Divide each side by '13'. y = -1 Simplifying y = -1
| 2(3x-4)+7=-4(3x-2) | | 787.5+4.9x=875+3.5x | | (u-8)*10=18 | | 1000x=281421906 | | b+2b+3b-22=4(b+6) | | -26=13t | | -16=6x-1 | | -6v+4(v+3)=-4 | | 400x=1000 | | 7a^2-42=35a | | 33=y+16 | | 12x^3+68x^2+84x= | | 5(n-3)=7+3m | | (6x-3-4)=(4x+14) | | 2x+32+x^2=80 | | 28*60=14x | | 125x-8x^4= | | 42=4n-7(n-9) | | 2x-22=-8 | | (6x-34)=(4x+14) | | x^3+4*x^2+6x+1=0 | | 2x+2x+(x+10)+50=40 | | (q-8)*5=10 | | 11x-18y=8 | | 6x*ln(x^3)=0 | | 18x+30y=24 | | 6x+123=102.6+8.55x | | 4a-6whena=8 | | 3x-16=3x | | 18=(2x-6) | | 3y=-4x-16 | | X+15-3(x+2)=-11 |